Cross-border cooperation on CO2 transport and sequestration: the case of Germany and Norway - Dickel, R; Fattouh, B; Muslemani, H (Oxford Institute for Energy Studies, 2022)
If two different jurisdictions are involved in the Carbon Capture and Storage (CCS) chain, CO2 handling needs to be harmonized across borders and interface issues should be resolved (e.g. technical and operational standards, certification, transfer of ownership and risk, etc.). Similar to the imbalance which exists between the demand for fossil fuels between importing and exporting countries, suitable geological formations for CO2 storage may not exist in the highest-emitting countries, which calls for a need to export CO2 to countries with more suitable storage sites. It may also be in the interest of fossil fuel exporting countries to help their customers to dispose of CO2 stemming from imported hydrocarbons, as importing countries may have no other option due to the lack of sequestration potential (e.g. Japan). This will involve exporting and importing of CO2 across borders, relying on offshore transport by ships or via pipelines in most cases. Thus far, such examples include the transport of CO2 by onshore pipelines from the Boundary Dam project in Canada to the Weyburn project in the US, and the upcoming Longship project which envisages cross-border transport of CO2 via shipping from the UK and EU countries to Norway. All other projects so far have been within one jurisdiction. However, most recently (August 2022), Northern Lights signed a first-of-its-kind commercial agreement for cross-border CO2 capture and transport, where, from 2025, CO2 will be captured, compressed and liquified in the Netherlands, to be transported and stored in Norway. It is expected that other similar ventures will be established, making the publication of this study all the more timely.